Fungicide, insecticide, and foliar fertilizer effect on soybean yield, seed composition, and canopy retention. Issue 2 (5th January 2021) - Bergman, Kelsey; Ciampitti, Ignacio; Sexton, Peter; Kovács, Péter
Abstract: Soybean [ Glycine max (L.) Merr.] yield has increased over time through the introduction of new varieties and improved agronomic practices. However, seed protein concentration has decreased. We conducted field studies in 2018 and 2019 to investigate the effects of fungicide, insecticide, and foliar fertilizer application on grain yield and seed quality in two soybean maturity groups (MG). In‐season treatments targeted nutrient availability and soybean canopy duration during the seed‐filling period by fungicide, insecticide, or foliar fertilizer application at the onset of this period. Biomass samples were collected at R5, R6, and R7 and partitioned into plant parts. Year, location, and MG often influenced yield and seed composition, but foliar fungicide, insecticide, or fertilizer application had no impact on these parameters. Core Ideas: Yield did not improve with use of crop protection in low pest pressure environments. Seed composition did not improve in low pest pressure conditions. Reproductive biomass partitioning did not change with foliar protection applications. Slight improvement in leaf retention was seen with R3 fungicide and insecticide applications.